Electrical Properties of Sr1–xBixFe0.6Sn0.4O3 Thermistor Ceramics. (8th April 2015) - Yuan, Changlai; Yang, Tao; Chen, Guohua; Zhou, Changrong; Yang, Yun; Zhou, Xiujuan
Abstract : Bi x Sr1− x Fe0.6 Sn0.4 O3 (0.2 ≤  x  ≤ 0.6) thermistor ceramics were prepared by conventional solid‐state reaction method. The Bi substitution affected the crystalline structure and induced the decrease of lattice parameters a, b, and c in Bi x Sr1− x Fe0.6 Sn0.4 O3 ceramics, except for x  = 0.6. The values of room‐temperature resistivity, thermistor constant, and activation energy of Bi x Sr1− x Fe0.6 Sn0.4 O3 ceramics were 7.05–6790 kΩ.cm, 4375–6694 K, and 0.378–0.578 eV, respectively. Electrical microstructural analysis indicated that in ceramic surface layers, grain boundaries, and grain cores of the thermistor ceramics, Ohmic behavior was the main conductive mechanism and space‐charge effect was dominant in grain shells.